Assessment and analysis of agricultural non-point source pollution loads in China: 1978–2017. (1st June 2020) - Zou, Lilin; Liu, Yansui; Wang, Yongsheng; Hu, Xuedong
Abstract: China's successful agriculture development has resulted in public concerned environmental problems. However, continuous and detailed data about Chinese agricultural non-point source pollution (ANPSP) loads are lacking. To assess and analyze Chinese ANPSP loads from 1978 to 2017, an inventory analysis was performed, and a socioeconomic and spatiotemporal analysis in the scale of provinces was conducted. The results showed that the pollution loads of chemical oxygen demand (COD), total nitrogen (TN) and total phosphorus (TP) increased by 91.0%, 196.2% and 244.1%, respectively, and their variation underwent a free development stage, reform promotion stage, market regulation stage and policy incentive stage. The results of the pollution source analysis showed that over the past 40 years, the total percent contribution to COD by livestock and poultry breeding (LPB) and rural household waste (RHW) accounted for 83.1%–96.6%, the total percent contribution to TN by mineral fertilizers (MF) and LPB accounted for 72.3%–80.8%, and the total percent contribution to TP by LPB, RHW and MF accounted for 69.1%–88.6%. In addition, Shandong, Guangdong, Sichuan, and Henan were the top producers of ANPSP loads, and their COD, TN, and TP loads accounted for approximately 32%, 30%, and 35% of the national totals, respectively. The discharge intensity of COD, TN and TP decreased by 79.2%, 67.8%, and 62.6%, respectively. The discharge intensity exhibited a phasic feature that aligned with the national economic plan in the temporal scale and was closely related to the agricultural conditions in the spatial scale. Highlights: Agricultural non-point source pollution loads from 1978 to 2017 were estimated. Total pollution loads increase by 114% and discharge intensity decreases by 70%. The periodic growth characteristic of pollution loads is divided into four stages. China's agricultural policies relevantly decreased the discharge intensity.